2008
DOI: 10.1016/j.jana.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of a Mind-Body Intervention for People Living With HIV

Abstract: Stress and anxiety are significant problems for individuals living with HIV. Mind-body therapies such as progressive muscle relaxation training and guided imagery (PMRT-GI) are effective in treating stress and anxiety in chronically ill persons. The purpose of this study was to identify key elements of an effective and culturally acceptable PMRT-GI intervention for economically disadvantaged persons with HIV. PMRT-GI was provided to 24 participants from African American, White, and Hispanic backgrounds. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are only limited examples of research focused specifically on investigating the potential efficacy of mind-body interventions for African Americans. A handful of studies have examined mind-body practices such as progressive muscle relaxation and yoga for health conditions such as pregnancy, breast cancer, HIV, and hypertension in African Americans (Andrade & Anderson, 2008; Jallo, Bourguignon, Taylor, & Utz, 2008; Moadel et al, 2007; Pullen et al, 2009). A research program based at the University of Iowa has demonstrated the benefits of transcendental meditation, which involves focusing on a mantra (or purposeful and silent word or phrase) to quiet the mind and promote relaxation, for improving blood pressure management (reduced blood pressure and reduced need for blood pressure medication) among African Americans with hypertension (Schneider et al, 2005).…”
Section: The Need For Solution-oriented Researchmentioning
confidence: 99%
“…There are only limited examples of research focused specifically on investigating the potential efficacy of mind-body interventions for African Americans. A handful of studies have examined mind-body practices such as progressive muscle relaxation and yoga for health conditions such as pregnancy, breast cancer, HIV, and hypertension in African Americans (Andrade & Anderson, 2008; Jallo, Bourguignon, Taylor, & Utz, 2008; Moadel et al, 2007; Pullen et al, 2009). A research program based at the University of Iowa has demonstrated the benefits of transcendental meditation, which involves focusing on a mantra (or purposeful and silent word or phrase) to quiet the mind and promote relaxation, for improving blood pressure management (reduced blood pressure and reduced need for blood pressure medication) among African Americans with hypertension (Schneider et al, 2005).…”
Section: The Need For Solution-oriented Researchmentioning
confidence: 99%
“…Research in most cultures finds that people living with HIV/AIDS face significant psychological and social problems in addition to their physical ones (Sun et al, 2007;Andrade and Anderson, 2008). AIDS-related stigma and discrimination have been seen all over the world, although they manifest themselves differently between countries, communities, religious groups and individuals.…”
Section: Impact Of Stigmamentioning
confidence: 99%
“…Kamenga et al 1991, Tsertsvadze et al 2008, Ferguson et al 2009). Interventions that provide information and referrals about complimentary or alternative medication (MacIntyre & Holzemer 1997, Andrade & Anderson 2008) may be helpful to families struggling with common uncertainties and transitional patterns (Knafl 2011).…”
Section: Conceptualizing the Hiv/aidss Disease Trajectorymentioning
confidence: 99%